2022
DOI: 10.17796/1053-4625-46.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Habits and its Association with Malocclusion in Primary Dentition among School Going Children of Nepal

Abstract: Objectives: The objectives of this study were to: (1) study the prevalence of oral habits among school going children with primary dentition; (2) determine the association of oral habits with malocclusion in primary dentition; and (3) compare the prevalence of oral habits based on gender, race, age and grade. Study design: A community based cross-sectional study was conducted among 625 school going children with a complete set of primary dentitions. A closed-ended questionnaire was developed to gather informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although NNSH may provide some benefcial efects, it has more adverse outcomes than positive ones. Some of these negative efects may be related to dentition, such as the development of dental caries and tooth malalignment [7][8][9]. However, others are related to the child's general health and alteration of the oral and gastrointestinal microbiota, which leads to increased infection [10] and asthma [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although NNSH may provide some benefcial efects, it has more adverse outcomes than positive ones. Some of these negative efects may be related to dentition, such as the development of dental caries and tooth malalignment [7][8][9]. However, others are related to the child's general health and alteration of the oral and gastrointestinal microbiota, which leads to increased infection [10] and asthma [11].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Schmid et al [ 29 ] concluded that prolonged pacifier use (approximately 3 years) can lead to an open bite and posterior crossbite. Rai et al [ 30 ] found among children in Nepal a significant association with crossbite with p = 0.01. However, we have not found a statistically significant relationship in the vertical plane but we agree in the horizontal plane between pacifier use for more than 2 years and the appearance of posterior crossbite, both unilaterally and bilaterally.…”
Section: Discussionmentioning
confidence: 99%
“…Lip-biting was also correlated with crowding in the present study. However, a study conducted in Nepal focusing on oral habits and malocclusion among 3- to 7-year-olds found no association between crowding and lip habits [ 39 ]. The inconsistent finding may be explained by the teeth movement caused by the force of perilabial muscles.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may be attributed to different diagnostic criteria used in those studies, which defined increased overjet as >3 mm in comparison to the 4 mm used in the current study. However, there were no established diagnostic criteria for increased overjet, and the cutoff point (>4 mm) was also used in other studies [ 20 , 39 ].…”
Section: Discussionmentioning
confidence: 99%